2018
DOI: 10.3390/ijms19051451
|View full text |Cite
|
Sign up to set email alerts
|

SOX7 Target Genes and Their Contribution to Its Tumor Suppressive Function

Abstract: SOX7 is a transcription factor and acts as a tumor suppressor, but its target genes in cancers are poorly explored. We revealed SOX7-mediated gene expression profile in breast cancer cells using microarray chips and discovered multiple altered signaling pathways. When combinatorially analyzing the microarray data with a gene array dataset from 759 breast cancer patients, we identified four genes as potential targets of SOX7 and validated them by quantitative PCR and chromatin immunoprecipitation assays. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In addition to activating p53, lncRNA MEG3 can improve the apoptosis of the tumor cells by reducing Bcl-xL (Liu et al, 2015). Besides, the transcription factor SOX7 acts as tumor suppressor in NSCLC possibly through activating SPRY1 and SLIT2, and repressing TRIB3 and MTHFD2 (Hayano et al, 2013;Zhang et al, 2018). MEG3 can enhance the sensitivity to DDP of NSCLC via MEG3/miR-21-5p/SOX7 axis (Wang et al, 2017a).…”
Section: Downregulated Lncrnas In Nsclc Ddp Resistancementioning
confidence: 99%
“…In addition to activating p53, lncRNA MEG3 can improve the apoptosis of the tumor cells by reducing Bcl-xL (Liu et al, 2015). Besides, the transcription factor SOX7 acts as tumor suppressor in NSCLC possibly through activating SPRY1 and SLIT2, and repressing TRIB3 and MTHFD2 (Hayano et al, 2013;Zhang et al, 2018). MEG3 can enhance the sensitivity to DDP of NSCLC via MEG3/miR-21-5p/SOX7 axis (Wang et al, 2017a).…”
Section: Downregulated Lncrnas In Nsclc Ddp Resistancementioning
confidence: 99%
“…11 To determine whether Sox7 physically interacts with PSME in vivo, we carried out ChIP analysis in C4-2 cells with ectopic Sox7 expression using a ChIP-validated anti-Sox7 antibody. 25 Our data indicated that anti-Sox7 antibody preferentially precipitated the genomic region containing PSME compared to IgG control antibody ( Figure 3A). Furthermore, this difference was not observed when we used the same antibody pairs against a genomic region on chromosome 8 (SNP28254).…”
Section: Sox7 Interacts With Psme In Vivo and Negatively Regulates mentioning
confidence: 71%
“…PSMA expression is stimulated by an enhancer element, PSME , in prostate cells, which contains several potential binding sites for Sox proteins . To determine whether Sox7 physically interacts with PSME in vivo, we carried out ChIP analysis in C4‐2 cells with ectopic Sox7 expression using a ChIP‐validated anti‐Sox7 antibody . Our data indicated that anti‐Sox7 antibody preferentially precipitated the genomic region containing PSME compared to IgG control antibody (Figure A).…”
Section: Resultsmentioning
confidence: 94%
“…One is Sox7 that activates its targeted genes, such as SPRY1 and SLIT2 by serving as a transcriptional factor. 46 The other is Sox7 antagonism of Wnt/β-catenin signaling, a commonly upregulated pathway in human cancers involved in the regulation of cell proliferation, survival, and migration. 45 , 47 , 48 But the precise molecular mechanism behind these effects remains unclear.…”
Section: Discussionmentioning
confidence: 99%